2011
DOI: 10.1074/jbc.m111.229831
|View full text |Cite
|
Sign up to set email alerts
|

DLK1-DIO3 Genomic Imprinted MicroRNA Cluster at 14q32.2 Defines a Stemlike Subtype of Hepatocellular Carcinoma Associated with Poor Survival

Abstract: Hepatocellular carcinoma (HCC) is a heterogeneous and highly aggressive malignancy, for which there are no effective cures. Identification of a malignant stemlike subtype of HCC may offer patients with a dismal prognosis a potential targeted therapy using c-MET and Wnt pathway inhibitors. MicroRNAs (miRNAs) show promise as diagnostic and prognostic tools for cancer detection and stratification. Using a TRE-c-Met-driven transgenic HCC mouse model, we identified a cluster of 23 miRNAs that is encoded within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 39 publications
5
123
1
Order By: Relevance
“…Although it would be interesting to establish whether the paternal or maternal imprinted alleles were dysregulated by gene targeting, this could not be determined in the inbred mouse strain used in our experiments. The HCCs produced by Rian gene targeting were remarkably similar to the C3 subclass of human HCCs identified by micro-RNA profiling (17,18), demonstrating the accuracy of in vivo gene targeting for modeling human cancer. These similarities included an aggressive phenotype with vascular invasion, AFP and EPCAM expression, activated PI3K/AKT signaling, and an identical domain of increased gene expression within the imprinted BEGAIN-DIO3 locus.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Although it would be interesting to establish whether the paternal or maternal imprinted alleles were dysregulated by gene targeting, this could not be determined in the inbred mouse strain used in our experiments. The HCCs produced by Rian gene targeting were remarkably similar to the C3 subclass of human HCCs identified by micro-RNA profiling (17,18), demonstrating the accuracy of in vivo gene targeting for modeling human cancer. These similarities included an aggressive phenotype with vascular invasion, AFP and EPCAM expression, activated PI3K/AKT signaling, and an identical domain of increased gene expression within the imprinted BEGAIN-DIO3 locus.…”
Section: Discussionmentioning
confidence: 75%
“…1A). A recent report showed that c-Met overexpression in transgenic mice can also induce Afp + HCCs that express Dlk1 and a subset (23 of 42) of the Rian-Mirg microRNAs (18). However, in this model additional secondary mutations are required for HCC formation (39), and c-Met was not overexpressed in the mouse tumors we produced by gene targeting (Table S3).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The latter are part of the mir-379/mir-656 miRNA cluster, a chromosomal region that appears increasingly more relevant to normal placental development [17][18][19] and fetal growth, 20 stem cell differentiation 21 and various pathological conditions. [22][23][24] Further statistical analyses identified additional imprinted genes as specifically related to the placenta and hemangioma: PLAGL1, DIO3OS, TFPI2, GRB14, H19 and MEG3. If the role of imprinted genes in placental development was already well established, it is, to our knowledge, the first assessment of them in infantile hemangiomas.…”
Section: Modern Pathology (2013) 26 247-255mentioning
confidence: 99%